Paediatric Emergency Triage, Assessment and Treatment (ETAT) - preparedness for implementation at primary care facilities in Malawi - Carina King; Albert Dube; Beatiwel Zadutsa; Lumbani Banda; Josephine Langton; Nicola Desmond; Norman Lufesi; Charles Makwenda; Helena Hildenwall (Taylor & Francis Group, 2021)
Background The majority of deaths amongst children under 5 years are still due to preventable infectious causes. Emergency care has been identified as a key health system weakness, and referrals are often challenging. Objective We aimed to establish how prepared frontline facilities in Malawi are to implement WHO Emergency Triage Assessment and Treatment (ETAT) guidelines, to support policy and planning decisions. Methods We conducted a concurrent mixed-methods study, including facility audit; healthcare provider survey; focus group discussions (FGD) and semi-structured interviews with facility staff. The study was conducted in two districts in Malawi, Zomba and Mchinji, between January and May 2019. We included all frontline facilities, including dispensaries, primary health centres, rural and community hospitals. Quantitative data were described using proportions, means and linear regression. Qualitative data was analysed using a framework approach. Data were analysed separately and then triangulated into common themes. Results Forty-seven facilities and 531 healthcare providers were included in the audit and survey; 6 FGDs and 5 interviews were completed. Four common themes emerged: (1) current emergency case management; (2) referral practices; (3) trained staff capacity; (4) opportunities and barriers for ETAT. Triage was conducted in most facilities with various methods described, and 53% reporting all staff are responsible. Referrals were common, but challenging due to issues in transportation. Twelve percent of survey respondents had ETAT training, with clinical officers (41%) reporting this more frequently than other cadres. Training was associated with increased knowledge, independent of cadre. The main barriers to ETAT implementation were the lack of resources, but opportunities to improve quality of care were reported. Conclusions Malawian frontline facilities are already providing a level of emergency paediatric care, but issues in training, drug supplies and equipment were present. To effectively scale-up ETAT, policies need to include supply chain management, maintenance and strengthening referral communication.